(untitled) (Research, Society and Development, 2022)
Objective: To analyze the development of complications during hospitalization of patients with COVID-19 and HF. Method: This is an observational, quantitative study, based on the review of medical records of patients admitted to the Respiratory Diseases Unit (RDU) of a University Hospital in northeastern Brazil, with RT-PCR reagent for SARS-COV2 and diagnosis of HF. Results: Of the 77 patients, 51 (66.2%) had an acute chronic heart failure (CHF) while the others (n = 26; 33.8%) had no history of previous heart disease and were having their first episode of heart failure. acute (ICA). Those with the NYHA IV classification had a higher risk of developing shock (p = 0.001), cardiopulmonary arrest (CPA) (p = 0.01), acute respiratory distress syndrome (ARDS) (p < 0.0001), bacteremia (p = 0.008), hemorrhage and liver damage (p = 0.04) as complications. The in-hospital mortality rate was 39% (n=30). When analyzing the relationship between the type of complication developed and the outcome death, shock, CPA, ARDS (p < 0.0001), pneumonia (p = 0.009), bacteremia (p = 0.0003), hemorrhage, anemia (p = 0.02), cardiac arrhythmia (p = 0.03) and liver damage (p = 0.04) were significantly associated. Conclusion: The association between HF and COVID-19 on admission leads to a high in-hospital mortality rate. Patients with NYHA functional class IV have a higher risk of developing complications and death during hospitalization. In addition, patients with HF and COVID-19 who develop pneumonia, ARDS, shock, CA, anemia, hemorrhage, arrhythmia, liver damage, and/or bacteremia have a higher mortality rate.